The In Vitro Antioxidant and Antiadipogenic Properties of Pigmented Flower Extracts of Geraniaceae and Lamiaceae Plant Families - Anton Venter; Hennie Fisher; Gary I. Stafford; June C. Serem; Megan J. Bester; Kwaku G. Duodu (Journal of Chemistry)
This study investigated the potential health-promoting properties of new sources of natural food colorants, namely pigmented flower extracts from Geraniaceae (Pelargonium grandiflorum, Pelargonium × hortorum, Pelargonium zonale hybrid) and Lamiaceae (Salvia aurea × dolomitica, Salvia dolomitica and Plectranthus zuluensis). In the Geraniaceae family, the main phenolic acids identified were hydrolysable tannins, while the main flavonoids were rutinosides of kaempferol and quercetin. In the Lamiaceae family, the main phenolic acids were caffeic acid and its derivatives, and the main flavonoids were naringin and neohesperidin. The total polyphenol content (TPC) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity were higher for Geraniaceae than for Lamiaceae species. For all extracts, oxygen radical absorption capacity (ORAC) was similar, except for P. zonale hybrid. These extracts protected Caco-2 cells against 2, 2′-azobis (2-amidinopropane) dihydrochloride (AAPH) generated oxidative damage. Similarly, all extracts, except P. zonale hybrid, effectively scavenged nitric oxide (NO) and reduced lipopolysaccharide (LPS)-induced NO formation in RAW 264.7 macrophages. Inhibition of the formation of advanced glycation end-products (AGE) was significant for P. grandiflorum and P. × hortorum. All pigmented flower extracts, except the P. zonale hybrid, reduced lipid accumulation in differentiated 3T3-L1 adipocytes. Treatment during adipocyte differentiation caused cell death, except for the P. zonale hybrid. In conclusion, related to antioxidant activity, inhibition of AGE formation and lipid accumulation in differentiated adipocytes, P. grandiflorum was the most active, while the P. zonale hybrid was the least. These differences are potentially related to the concentration, type and stability of the polyphenols found in these pigmented flower extracts. Overall, the pigmented flower extracts of Geraniaceae and Lamiaceae show a range of health-promoting properties that represent an additional benefit to their potential use as natural food colourants.